2007
DOI: 10.1074/jbc.m607469200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-mediated Phosphorylation of the Calcium-sensing Receptor Is Stimulated by Receptor Activation and Attenuated by Calyculin-sensitive Phosphatase Activity

Abstract: The agonist sensitivity of the calcium-sensing receptor (CaR) can be altered by protein kinase C (PKC), with CaR residue Thr 888 contributing significantly to this effect. To determine whether CaR T888 is a substrate for PKC and whether receptor activation modulates such phosphorylation, a phospho-specific antibody against this residue was raised (CaR pT888 mobilization rather than oscillations (9). Whereas this suggests that PKC-mediated CaR phosphorylation regulates CaR function, no reagents have existed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 23 publications
4
56
0
Order By: Relevance
“…Phosphomimetic substitution of this site (CaR T888D ) lowers the Ca 2ϩ o sensitivity of the receptor (13) while nonphosphorylatable CaR T888A is more sensitive to Ca 2ϩ o and promotes sustained rather than oscillatory Ca 2ϩ i mobilization (14,15). This is the basis for the hypothesis that dynamic CaR T888 phosphorylation is required for oscillatory Ca 2ϩ i mobilization, an effect that had been proposed previously for other class C G proteincoupled receptors (16 -18).…”
mentioning
confidence: 77%
“…Phosphomimetic substitution of this site (CaR T888D ) lowers the Ca 2ϩ o sensitivity of the receptor (13) while nonphosphorylatable CaR T888A is more sensitive to Ca 2ϩ o and promotes sustained rather than oscillatory Ca 2ϩ i mobilization (14,15). This is the basis for the hypothesis that dynamic CaR T888 phosphorylation is required for oscillatory Ca 2ϩ i mobilization, an effect that had been proposed previously for other class C G proteincoupled receptors (16 -18).…”
mentioning
confidence: 77%
“…Given that the mutants 3E2 and 3E3, which similarly failed to interact with CaM, still preserve reduced Ca 2ϩ responses, it is likely that deletion of this region has adverse effects on the structural integrity and functionality of other regions of the cytoplasmic tail of CaSR, which also contribute to the Ca 2ϩ response. It has been reported that increases of extracellular Ca 2ϩ to 2-3 mM can induce intracellular Ca 2ϩ oscillations in HEK293 cells expressing CaSR (31)(32)(33). We then examined the [Ca 2ϩ ] i oscillatory frequencies in HEK293 cells transfected with CaSR and its mutants.…”
Section: Structural Changes During Camtarget Complex Formation Andmentioning
confidence: 99%
“…2; wt, 3.0G0.1 mM; T888M, 2.5G0.2 mM; P!0.05 by unpaired t-test of log EC 50 values). Western blotting revealed similar expression of protein bands consistent with the wellrecognized 140 kDa core-glycosylated and 160 kDa mature receptors (7,(12)(13)(14)(15)20) in both sets of transfected cells (Fig. 2C).…”
Section: T888m Mutation In Hek-293 Cellsmentioning
confidence: 66%
“…This mutation was predicted by PolyPhen (prediction of functional effect of human nsSNPs; http://genetics. bwh.harvard.edu/pph/) to have a position-specific independent counts (PSIC) score of 1.711, and modeling of the effect on the amino acid sequence of the CASR protein predicted a substitution of methionine for threonine at position 888 (p.T888M) that would abolish a major intracellular PKC phosphorylation site (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation